Student Perspective on Employability Skills in Business Education - Hisham Kamil Madi; Fadi Abdelfattah; Maryam Al-Washahi; Ahmad Abdel Qader (Emerging Science Journal, 2025)
This study aims to examine how academic motivation and perceived relevance of curriculum influence career readiness and perceived employability skills among business students in Omani higher education institutions. It further investigates the mediating roles of skill development perception and learning engagement, and the moderating role of internship opportunities in these relationships. A quantitative survey-based approach was employed, collecting data from 386 business students using stratified random sampling to ensure representation across academic programs. Data were analyzed using SmartPLS-based Structural Equation Modeling (SEM), incorporating Confirmatory Factor Analysis, mediation, and moderation analyses. The findings reveal that both academic motivation and perceived curriculum relevance significantly enhance career readiness and employability skills, with skill development perception and learning engagement serving as significant mediators. Internship opportunities strengthen these effects, demonstrating their role as a key moderator. The novelty of this research lies in integrating motivational, curricular, and experiential factors within a single empirical framework for the Omani higher education context. The study contributes practical recommendations for curriculum design, teaching practices, and industry-academia collaboration, while providing policymakers with evidence-based insights to bridge the skills gap and better prepare graduates for the evolving labor market.